Pelvic floor disorder and relevant factors in Iranian women of reproductive age: a cross-sectional study - Fatemeh Rashidi; Mojgan Mirghafourvand (BMC, 2023)
Abstract Background With high severity and prevalence, pelvic floor disorder is a health issue that women face worldwide. Different demographic-obstetric factors are involved in the emergence of this dysfunction that can have many adverse effects on a woman's quality of life. Hence, this study aimed to determine the prevalence of pelvic floor disorder and its related socio-demographic and obstetric factors among Iranian women of reproductive age. Methods The statistical population of this cross-sectional study included 400 woman of reproductive age (15-49 years) covered by the health centers of Tabriz, Iran in 2022. The cluster sampling method was employed to select the participants. The data collection tools were a socio-demographic and obstetric characteristics questionnaire and the PDFI-20 (Pelvic Floor Distress Inventory-20). The chi-squared test was conducted to determine the association between socio-demographic and obstetric characteristics and prevalence of pelvic floor disorder in a bivariate analysis, whereas the multivariate logistic regression test was used in a multivariate analysis. Results The general prevalence of pelvic floor disorder was 76%. The prevalence rates of pelvic organ prolapse distress 6 (POPDI-6), colorectal-anal distress 8 (CRAD-8), and urinary distress (UDI-6) were 54.3%, 61.8%, and 49.3%, respectively. The results of the multivariate logistic regression test indicated that constipation (odds ratio = 5.62; 95% CI 1.97 to 16.03; P = 0.001) increased the risk of pelvic floor disorder. Conclusions According to the findings, the prevalence of pelvic floor disorder is high among Iranian women of reproductive age. This condition is correlated with constipation. Therefore, screening is recommended through valid tools in addition to offering preventive measures such as preventing and curing constipation to reduce the risk of pelvic floor disorder.